2017
DOI: 10.18805/ijar.v0iof.9154
|View full text |Cite
|
Sign up to set email alerts
|

Economics of feeding protected protein and protected fat on crossbred cattle

Abstract: A study was undertaken to evaluate the economics of feeding protected protein and protected fat in crossbred cows. The feeding trial of 4 months duration was conducted on 24 crossbred cattle which were subjected to treatment T 0 (Control), T 1 (Protectedprotein), T 2 ( Protected fat) and T 3 (Protected protein and fat) . Crossbred cows in second to fourth lactation with most probable production ability (MPPA) of average 2300 liter milk production per lactation for each group were selected. All animals were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…The present findings demonstrated that NPN content in CPMSG was much higher compared with that in soybean meal (T1 treatment), so the rate of nitrogen release from soybean meal was lower than that from T2 and T3 treatments particularly after 4 h post feeding. Moreover, CPMSG may synchronize the ammonia and energy availability to improve microbial protein synthesis, thus amino acid or ammonia nitrogen will become transaminase or used directly for microbial synthesis and animals must be provided readily availablesource of different amino acids and carbohydrates to minimize negative energy balance (Bach et al 2005;Mane et al 2017). increase feed intake, crude protein digestibility, total VFA concentrations and growth performance of fattening animals.…”
Section: Resultsmentioning
confidence: 99%
“…The present findings demonstrated that NPN content in CPMSG was much higher compared with that in soybean meal (T1 treatment), so the rate of nitrogen release from soybean meal was lower than that from T2 and T3 treatments particularly after 4 h post feeding. Moreover, CPMSG may synchronize the ammonia and energy availability to improve microbial protein synthesis, thus amino acid or ammonia nitrogen will become transaminase or used directly for microbial synthesis and animals must be provided readily availablesource of different amino acids and carbohydrates to minimize negative energy balance (Bach et al 2005;Mane et al 2017). increase feed intake, crude protein digestibility, total VFA concentrations and growth performance of fattening animals.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been studies on the use of protected proteins and fats in the feeding of dairy cows [11]. Compared to the control, in the experimental groups with protected protein, a higher consumption of dry matter of feed was observed and, accordingly, an increase in milk productivity by 16.5 and 21.0 %.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…On an average, the total feed cost (Rs.) per animal per day during the experimental period in CON and MO was 191.80and 206.14 (Naik et al, 2009); 36/-per buffalo per day (Parnerkar et al, 2011); 46.91/-per buffalo per day (Shelke and Thakur, 2011); 11.60/-per cow per day (Gowda et al, 2013); 15.53/-per buffalo per day (Vahora et al, 2013); 23.70/-per animal per day (Amrutkar et al,2014); 11.05/-per animal per day (Grewal et al,2014); 50/-per cow per day (Singh et al, 2014); 94.46/-per cow per day (Yadav et al, 2015); 62.07/-per cow per day (Mane et al, 2017) and 127.49/-per cow per day (Parihar et al, 2018).…”
Section: Economics Of Milk Productionmentioning
confidence: 99%
“…To counter affect the demerits of higher levels of concentrate feeding as acidosis and decline in concentration of milk fat; supplementing fat in the diet has become a standard practice to fulfil the energy requirements of dairy cows. Supplementation of fat might increase the cost of feeding but net return per animal may also increase due to increase in milk yields and milk fat apart from its positive effect on reproduction and health of animal (Mane et al, 2017). The cost of feeding per litre milk production is a significant factor in governing the economic viability of livestock sector which must be reduced by adopting new measures in the ration formulation.…”
Section: Introductionmentioning
confidence: 99%